Piezoelectric Biomaterial with Advanced Design for Tissue Infection Repair - Siyuan Shang; Fuyuan Zheng; Wen Tan; Zhengyi Xing; Siyu Chen; Fuli Peng; Xiang Lv; Duan Wang; Xiangdong Zhu; Jiagang Wu; Zongke Zhou; Xingdong Zhang; et al. (Advanced Science)
Abstract Bacterial infection has become the most dangerous factor in tissue repair, which strongly affects the tissue regeneration efficiency and wellness of patients. Piezoelectric materials exhibit the outstanding advantage of producing electrons without external power supply. The ability of electron enrichment and reactive oxygen species generation through noninvasive stimulations enables piezoelectric materials the potential applications of antibacterial. Many studies have proved the feasibility of piezoelectric materials as a functional addition in antibacterial biomaterial. In fact, numerous piezoelectric materials with ingenious designs are reported to be effective in antibacterial processes. This review summarizes the antibacterial mechanisms of piezoelectric, illuminating their potential in combating bacteria. Recent advancement in the design and construction of piezoelectric biomaterial including defect engineering, heterojunction, synergy with metal and the composite scaffold configuration are thoroughly reviewed. Moreover, the applications and therapeutic effects of piezoelectric materials in common tissues with antibacterial requirements are introduced, such as orthopedics, dental, and wound healing. Finally, the development prospects and points deserving further exploration are listed. This review is expected to provide valuable insight into the relationship between antibacterial processes and piezoelectric materials, further inspiring constructive development in this emerging scientific discipline.